PANCASILA AMID THE FLOW OF DIGITAL NEGATIVITY: STUDENTS’ INTERPRETATION IN A PHENOMENOLOGICAL STUDY - Indrawati Syamsuddin (Penelitian dan Pengembangan Ilmu, 2026)
The rapid development of digital technology has significantly transformed patterns of social interaction, particularly among university students, who represent one of the most active groups of social media users. Social media has become a digital public sphere that enables individuals to express opinions, participate in public discussions, and access information quickly. However, the growth of freedom of expression in digital spaces has also been accompanied by an increase in various forms of digital negativity, such as hate speech, destructive comments, cyberbullying, the spread of hoaxes, and communication practices that fail to reflect social ethics. This phenomenon poses challenges to the implementation of Pancasila values, which emphasize humanity, unity, tolerance, and respect for differences. This study aims to reveal and understand students’ interpretation of the phenomenon of digital negativity from the perspective of Pancasila values. This study used a qualitative approach with a phenomenological method to explore the lived experiences of students in facing the flow of digital negativity on social media. The research informants consisted of eight active students selected purposely based on the intensity of their social media use and their experiences interacting with negative content in digital spaces. Data were collected through in-depth interviews, observation, and documentation, then analyzed using Moustakas’ phenomenological model through the stages of epoche, horizontalization, thematic clustering, textural description, structural description, and the synthesis of the essence of experience. The results show that students interpret digital negativity as a phenomenon that is increasingly normalized in everyday digital life. Experiences of interacting with negative comments, hate speech, and digital conflict shape students’ critical awareness of the importance of communication ethics on social media. Students view freedom of expression in digital spaces as often being interpreted excessively, thereby disregarding the values of humanity and unity. On the other hand, Pancasila is still perceived as a relevant moral guideline for building a healthy digital communication culture, even though its implementation faces various challenges due to the development of an increasingly individualistic and emotional digital culture. This study confirms the importance of strengthening digital literacy grounded in Pancasila values as an effort to build ethical, critical, and responsible digital citizenship.